Cardiac myeloperoxidase activity is elevated in hypertensive pregnant rats - Zhu, Ming-lin; Zhao, Jin-ping; Cui, Ning; Gonçalves-Rizzi, Victor H. [UNESP]; Possomato-Vieira, Jose S. [UNESP]; Nascimento, Regina A. [UNESP]; Dias-Junior, Carlos A. [UNESP] (Springer Nature, 2017)
Myeloperoxidase (MPO) is released from activated neutrophils. The inflammation in preeclampsia was found to be associated with endothelial dysfunction. We hypothesized that cardiac and circulating MPO levels are elevated in hypertensive pregnancy. Systolic and diastolic blood pressure and heart rate were measured on pregnancy days 14, 16, 18 and 20 in normal pregnant and hypertensive pregnant rats. Left and right ventricle weights, the number of viable fetuses, litter size, fetal and placenta weights were recorded on gestational day 21. Circulating and cardiac MPO activities, soluble fms-like tyrosine kinase-1 (sFlt-1) and vascular endothelial growth factor (VEGF) and nitric oxide (NO) were detected. The results showed increases in cardiac (left, but not right ventricle) and circulating MPO activities, and concomitantly lower number of viable fetuses, litter size, and fetal and placenta weights, and decreases in NO in hypertensive pregnant rats. Also, the increases in circulating sFlt-1 and VEGF were found in hypertensive pregnant group. In conclusion, maternal and fetal detrimental changes along with increases in circulating sFlt-1 and VEGF in hypertensive pregnancy may be associated with increases in cardiac and circulating MPO activities, confirming the causative role of inflammatory response in preeclampsia.
Keywords: hypertensive pregnancy; myeloperoxidase; preeclampsia; rats